Remodeling of the Proximal Tibia Subsequent to Bone Graft Harvest: Postoperative CT Study. (July 2015) - Vanryckeghem, Vincent; Vandeputte, Geoffroy; Heylen, Steven; Somville, Johan
Background: Proximal tibia bone autograft (PTBG) is regularly used in reconstructive foot, ankle, and maxillofacial surgery. Although many surgeons prefer PTBG rather than the conventional iliac crest, little is known about the remodeling capacity of the proximal tibia after harvesting cancellous bone. Methods: Via bilateral postoperative computed tomography of 17 harvesting sites, comparing the defect side with the healthy side, we measured the repair capacity of the proximal tibia in response to bone defect created by the harvest at medium-term follow-up (mean 29 months; range, 7-55 months). Results: 16 of 17 (94%) cortical defects showed complete consolidation. Cancellous remodeling was graded 0 to 3, with 2 defects showing complete remodeling (grade 3), 4 defects partial remodeling (more than 50%), 8 defects partial remodeling (less than 50%) and 3 defects no remodeling at all (grade 0). Conclusion: The proximal tibia has the potential to form new cancellous bone after cancellous bone graft harvesting. More data are required to identify possible variables influencing this remodeling capacity. When performing knee surgery, knee surgeons should take into account the relatively small defect size and the consolidation of the cortical window after proximal tibia bone harvesting. Level of Evidence: Level IV, case series.